Translational Research in Cystic Fibrosis: From Bench to Beside - Garcia, Laura de Castro e; Petry, Lucas Montiel; Germani, Pedro Augusto Van Der Sand; Xavier, Luiza Fernandes; Barros, Paula Barros de; Meneses, Amanda da Silva; Prestes, Laura Menestrino; Bittencourt, Luana Braga; Pieta, Marina Puerari; Friedrich, Frederico; Pinto, Leonardo Araújo (Frontiers in Pediatrics, 2022)
Cystic fibrosis is the most common life-limiting recessive genetic disorder in Caucasian populations, characterized by the involvement of exocrine glands, causing multisystemic comorbidities. Since the first descriptions of pancreatic and pulmonary involvement in children, technological development and basic science research have allowed great advances in the diagnosis and treatment of cystic fibrosis. The great search for treatments that acted at the genetic level, despite not having found a cure for this disease, culminated in the creation of CFTR modulators, highly effective medications for certain groups of patients. However, there are still many obstacles behind the treatment of the disease to be discussed, given the wide variety of mutations and phenotypes involved and the difficulty of access that permeate these new therapies around the world.